Analisis Kemampuan Literasi Matematis Siswa pada Materi Operasi Aljabar di SMP Negeri 19 Pontianak - Rosandi, Oscar Oki; Saputro, Marhadi; Abdillah, Abdillah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze the mathematical literacy skills of students on algebraic operations material. The study uses a descriptive qualitative method with a case study format. The population in this research is the entire class VII C of SMP Negeri 19. Using purposive sampling techniques, a total population of 30 students was obtained, with 6 samples chosen as main subjects based on high, medium, and low mathematical literacy ability categories. The research instruments include mathematical literacy ability tests and interviews. The data analysis technique used is qualitative data analysis with stages of data reduction, data presentation, and conclusion drawing. The results of the study show that students with high mathematical literacy skills were able to meet all indicators of mathematical literacy ability, namely formulating, applying, and interpreting, although there were some errors in their written solutions. Students with medium literacy skills were able to understand the indicators of formulating and applying but still made technical errors in interpreting. Meanwhile, students with low mathematical literacy skills were only able to understand the formulating indicator.